Phonological Lexical Corpus of Czech and the Syllabic Structure of Czech Words - Bičan, Aleš (Bohemica Olomucensia, 2015)
The paper describes the Phonological Lexical Corpus of Czech (http://www.ujc.cas.cz/phword) and presents a sample of its analysis. The corpus is a phonologically transcribed database of lexical items from published dictionaries of Czech. Every item contains information about its length (in terms of phonemes and syllables), its syllabification, and phonological properties of the constituent phonemes. Information about the word's part of speech and its presence in various dictionaries is also included. As an example of the usefulness of the corpus, an analysis of the syllabic structure of Czech words is presented on the basis of 49 365 lexical items recorded in Slovník spisovné češtiny. Attention is paid to the co-occurrence of syllables according to the quality of the syllable nucleus, the presence vs. absence of the syllable coda, and the complexity of the syllable onset. It is demonstrated that there are certain tendencies in the distribution of syllables within words. First, the frequency of words decreases with the increase of non-short vowels within them. Second, words where one syllable is closed and the others are open are preferred to possible configurations. Third, Czech furthermore prefers words where exactly one syllable onset is complex and the others are simple.
Keywords: Phonological Lexical Corpus of Czech; syllabic structure of Czech words; distribution of syllables in Czech